The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10900-017-0432-6
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Work Ability and Health Problems Among Brazilian Recyclable Waste Pickers

Abstract: To describe the work ability and health problems among Brazilian recyclable waste pickers. Sixty-one workers answered questionnaires related to the work ability (Work Ability Index-WAI), musculoskeletal problems (Nordic Musculoskeletal Questionnaire-NMQ), low back related disability (Roland Morris Questionnaire-RMQ), physical activity (International Physical Activity Questionnaire-IPAQ), smoking (Fagerström Test for Nicotine Dependence-FTND), and alcohol use (The Alcohol Use Disorders Identification Test AUDIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
1
19
0
3
Order By: Relevance
“…Adverse health effects in waste recyclers have been studied in other developing countries [4,11], but there is limited research on this sector in South Africa. The health risks and injuries that are incurred by waste recyclers are a public health concern, which needs attention from all relevant stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adverse health effects in waste recyclers have been studied in other developing countries [4,11], but there is limited research on this sector in South Africa. The health risks and injuries that are incurred by waste recyclers are a public health concern, which needs attention from all relevant stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported associations between working at landfill sites and increased health risks, such as musculoskeletal disorders of the lower back, shoulders and neck [4]; upper and lower respiratory symptoms, with a high prevalence of coughs [5]; and mental health disorders [6]. A review by Binion and Gutbertlet (2012) reported an increased incidence of respiratory diseases among waste recyclers exposed to dust, fumes from chemicals and inhalation of sulphurous gases generated by anaerobic microbial decomposition of organic waste [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of them corroborates the idea that the precarious working conditions waste pickers live in are characterized by high socio-environmental vulnerability (aLENCaR;CaRDoSo;aNTUNES, 2009;BaLLESTERoS;aRaNGo E URREGo, 2012;CoELHo et al, 2016b;CoELHo et al, 2016c;SoUSa, MENDES, 2006). Moreover, such environment favors the occurrence of labor accidents (CaVaLCaNTE;FRaNCo, 2007;CoELHo et al, 2016c;SHIBaTa et al, 2015) and of physical and mental diseases (aLENCaR;CaRDoSo;aNTUNES, 2009;CoELHo et al, 2016b;aLVaRaDo-ESQUIVEL et al, 2008;aLVaRaDo-ESQUIVEL, 2013;aRaÚJo;SaTo, 2017;GUTBERLET;Ba-EDER, 2008;RoZMaN et al, 2008;SHIBaTa et al, 2015;SINGH;CHoKHaNDRE, 2015) capable of impairing their quality of life and health promotion.…”
Section: Chart 3 -List Of Articles Divided By Analytical Categorymentioning
confidence: 99%
“…The benefit and valorization of the Municipal Solid Waste (MSW) is an option that allows reincorporation into the productive cycle already discarded materials, which helps the performance of resources, to understand the problem of waste pickers garbage dump in the city of Puno. The prevention of the disease transcends the biological plane and positions itself in a social space for the individual (Kruta de Araújo & de Oliveira Sato, 2018), in which the most significant are the results that can generate for themselves, their work group and their family (Porras Bulla & Climent Sanjuán, 2018). In this context, recycling is a source of income for thousands of families (Cavé, (2013) ;Chen, et al, 2018), unfortunately in most cases, an informal source (Conke, 2019).…”
Section: Introductionmentioning
confidence: 99%